Puppet knowledge and the life of the puppeteer (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
How does one learn to become a puppeteer in a time when traditional forms seem outmoded, and new forms lack tradition? John Bell explores his own learning experiences with Peter Schumann's American troupe Bread & Puppet Theater, which combines avant-garde methods of invention with a strong respect for tradition, and explains how he combines both approaches in his own teaching, which wants to incorporate extensive knowledge of past practices of puppetry with an open approach to inventing new techniques with old and new forms of performing objects.Keywords: Puppetry. Education. Bread & Puppet Theater. Performing Objects.